The Status and Influencing Factors of Health Behavior Self‐Management in Children With Type 1 Diabetes Mellitus: A Cross‐Sectional Study - Jin‐Xia Yang; Yue Liu; Su‐ying Cao; Guo‐ying Wang; Hui‐min Zhou; Ya‐yun Wang; Zi‐sheng Ai (Health Science Reports)
ABSTRACT Background and Aims To investigate the status of self‐management of health behaviors in children with Type 1 diabetes mellitus and to analyze their influencing factors. Self‐management skills are essential for disease management in children with Type 1 diabetes. Methods This cross‐sectional study was conducted on 132 children with Type 1 diabetes mellitus hospitalized in the Department of Endocrinology and Genetic Metabolism of a tertiary children's hospital. Children were selected from September 2023 to March 2024 by convenience sampling method. A general information questionnaire and the Type 1 Diabetes Behavioral Rating Scale were used to conduct the questionnaire survey. Results The mean of health behavior self‐management score was (0.60 ± 0.15), and the mean scores of the four dimensions were: daily care behaviors (0.74 ± 0.16), adjustment of diabetes care behaviors (0.29 ± 0.24), diabetes care behavior intervention (0.52 ± 0.25), and other diabetes care behaviors (0.61 ± 0.27) points; one‐way analysis of variance showed that the differences in self‐management scores of health behaviors of children with Type 1 diabetes mellitus were statistically significant when comparing children with different ages, years since diagnosis, whether they were only children, family structure, whether there was a family member with a diagnosis of diabetes mellitus, literacy level of the parents, and average monthly family income (p < 0.05); the differences between age, whether they were only children, family structure, whether there was a family member with a diagnosed with diabetes mellitus, and average monthly family income were influential factors in the self‐management of health behaviors of children with Type 1 diabetes mellitus (p < 0.05). Conclusion The level of health behavior self‐management of children with Type 1 diabetes mellitus is in the middle‐low level, and individualized interventions can be carried out for children with different characteristics to promote the improvement of children's ability to manage their disease and improve their quality of life.